School Climate as Predictor of Upper Basic Business Studies Teacher Effectiveness in Delta State Schools - CHIAZOR, Patience Omavuotu; OFUME, Abigail Obiageli (Ilorin Journal of Education, 2023)
The study assessed school climate as a predictor of upper basic Business studies teachers’ effectiveness in Delta state schools. To guide the study, two research questions and one null hypothesis were raised. The population of the study consisted of all basic (public and private) in Delta state schools. A survey research design was employed for the study and a sample of one hundred (100) Business Studies teachers were selected using purposive and stratified random sampling. The instrument for the study was a school climate and teacher effectiveness questionnaire (SCATEQ) questionnaire. The instrument was validated by experts in the educational foundation at the University of Delta, Agbor. The reliability of the instrument was determined using Cronbach alpha and a coefficient of 0.76 was obtained. Mean and standard deviation was used to answer the research questions while Pearson product-moment correlation was used to test the hypothesis at a 0.05 level of significance. The findings of the study showed a significant relationship between school climate and teachers’ effectiveness. Based on the findings, it was recommended among others that the school’s physical environment consisting of facilities and others should be adequately provided to enhance Business studies teachers’ effectiveness.